Extraction and Identification Potent Antibacterial Bioactive Compound of Streptomyces sp. MB 106 from Euphorbia sp. Rhizosphere - Dian Rachma Wijayanti; Almatin Puspa Dewi (BIOEDUSCIENCE, 2022)
Background: Actinomycetes are groups of bacteria that play an important role in pharmacy and medicine in their ability to produce secondary metabolites in the form of bioactive compounds with various chemical structures and biological activities. The genus Streptomyces produces more than 70% of all described actinomycetes natural products. In particular, antibiotics represent the largest group. Through mutations, bacteria may survive chemotherapy. Thus its infection is hard to eradicate. Therefore the search for new potent bioactive compounds is important Methods: Isolate preparation, Production, and extraction bioactive compound, Crude extract antibacterial test, Identification of bioactive compound Results: There are antibacterial activities per 100 µl crude extract. Inhibition zone range from 11.5 to 13 mm. Various bioactive compounds detected in n-Butanol extract, There are nine bioactive compounds detected from Streptomyces sp. MB 106 crude extract. The highest was Naphthalene (43.89 %). The lowest was 3-Imino-3h,5h- [1,2,4] Thiadiazolo [3,4-1] Isoindole (1.70 %). Six compounds were reported to have antimicrobial activities butane, 1,1-dibutoxy, naphthalene, nonadecane, docosane, heneicosane, and eicosane Conclusions: Crude extract showed an average of 12 mm inhibition zone against Escherichia coli ATCC 8739. There are nine bioactive compounds from Streptomyces sp. MB 106. Six of them are promising drugs candidate. Further studies on these compounds are essential for future drugs candidate.